FEATURES OF MORPHOLOGICAL CHANGE IN NHA TRANG BEACH, KHANH HOA PROVINCE - Binh, Tran Van; Dan, Nguyen Dinh; Long, Bui Hong; Trung, Pham Ba; Cuong, Tran Minh; Hai, Nguyen Huu (Vietnam Journal of Marine Science and Technology, 2018)
This paper has focused on analyzing morphological change features of Nha Trang Beach based on the comparison of different beach profiles which were measured from July 2008 to September 2016 corresponding to the Northeast and Southwest monsoons. Additionally, the sediment transport balance was estimated by the method of equity value curve. Studied results show that the beach profiles were accreted and eroded during Southwest and Northeast monsoons respectively, but due to the shortage of materials supply, the beach has the narrowing trend. In this paper, some effects of the existing works in Nha Trang Beach such as Vinpearl, Navy Port, and hydro-dams in upstream area of Cai river have been also analyzed for estimating sedimentary supply to beach segments.